The h-extra conditional diagnosability of hypercubes under the PMC model and MM* model. Issue 3 (1st October 2016) - Zhu, Qiang; Zhang, Xing
ABSTRACT: Diagnosis plays an important role in maintaining reliability of multiprocessor systems. For a system G, Zhang et al. introduced h -extra conditional diagnosability, denoted by, which is a new measure of diagnosability. Under the PMC model, they obtained when and . In this paper, we extend their result and obtain that under the PMC model, when, . Under the MM model, Zhang et al. 's result on the h -extra conditional diagnosability is not right. In this paper, we first introduce the h -extra k -vertex-restricted diagnosability of a system G, denoted by, and showed that Zhang et al. determined the h -extra k -vertex-restricted diagnosability instead of the h -extra conditional diagnosability of . Then we extend their result under the MM model, and we have when, .